Integration of a course enrolment and class timetable scheduling in a student information system - Ajanovski, Vangel (AIRCCSE, 2013)
This paper is dealing with the most important issues of two of the most significant university administrative processes – the process of term enrolment with course enrolment and the process of organization of classes and scheduling a conflict-free class timetable. In the first part of the paper an introduction to the problem is set and the impact and interrelation of the two processes is explained in detail. In the second part of the paper, the focus is on the process of class timetable scheduling, with an analysis of how severe is the risk of having conflicts in the class schedule. Conflicts in the class schedule are rarely introduced due to the lack of resources, in the usual understanding of the term, but are mostly related to the availability human resources. The analysis gives more details on the probability that the students will have a conflict in the timetables among different courses they attend. The third part of the paper discusses some of the formal complexities of the course enrolment process and gives short overview of an earlier effort to overcome such complexities with an introduction of a virtual academic adviser. The virtual adviser components, are then integrated with a recommender system that gives each student personalized course recommendations based on historical data of courses and success. Finally, a solution is given in the form of a model that is currently under development in which a single unifying process is envisioned that covers both earlier processes. The integrated process defines a continuous dialogue between the student groups, enrolment administration and scheduling administration. It is expected from the solution to streamline both processes into a fully integrated system that will improve the student satisfaction from the organization and transparency of the administration.
Keywords: Administrative processes, Course Enrolments, Recommender Systems, Scheduling